Easy outdoor living : - Matthews, Clare (Hamlyn, 2007)
Imagine the possibilities for your garden! This sourcebook of innovative projects will turn any boring backyard into an extraordinary space for entertaining or relaxation. From the author of the bestselling Great Gardens for Kids, and illustrated by a prominent garden photographer, these enticing ideas require no special skills or tools. Just follow the straightforward instructions and practical photography to create a sari canopy to dress up an existing drab porch, a floral wind screen for a secluded spot, or a romantic chandelier bejeweled with crystal drops, ivy, and tea lights. Stylishly display your favorite plants or spruce up the kids’ play area—it’s all here, and easier than ever.